Validation of the spanish version of the childhood asthma control test (cACT) in a population of Hispanic children (2014)
Background: There is a critical need for additional validation studies of questionnaires designed to assess the level of control of asthma in pediatric patients. Objective: To validate the Spanish version of the Childhood Asthma Control Test (cACT) in children aged between 4 and 11 years with physician-diagnosed asthma. Methods: In a prospective cohort validation study, asthmatic children aged between 4 and 11 years and their parents, attended both a baseline and a follow-up visit 2 to 6 weeks later. In these two visits, they completed the information required to assess the criterion validity, construct validity, test-retest reliability, sensitivity to change, internal consistency and usability of the cACT. Results: At baseline, cACT scores were significantly different between patients with controlled, partly controlled and uncontrolled asthma [24.0 (23.0–26.0), 18.0 (18.0–22.0), and 17.5 (13.0–20.0), respectively, p < 0.001], and also between patients for whom this visit resulted in a step-up, no change or step-down in therapy [18.0 (15.0–21.0), 24.0 (23.0–24.0) and 26.0 (23.5–26.0) respectively, p < 0.001]. The score of the cACT correlated positively and significantly with the score of the Pediatric Asthma Caregivers Quality of life Questionnaire - PACQLQ (Spearman's rho = 0.50, p < 0.001). The intraclass correlation coefficient of the measurements in patients with no change in clinical status was 0.849 (95% CI: 0.752–0.908). There were statistical significant differences between baseline and follow-up cACT scores in patients with an improvement in clinical status [19.0 (18.0–22.0) versus 24.5 (24.0–25.0), p < 0.001]. Cronbach's α was 0.8276 for the questionnaire as a whole. Conclusion: The Spanish version of the cACT has adequate criterion validity, adequate construct validity, adequate sensitivity to change, good internal consistency, good test-retest reliability and excellent usability when administered to asthmatic children aged between 4 and 11 years.